ANALISIS KELAYAKAN USAHA PENAMPUNG GURITA (STUDI KASUS UD. MANDIRI DI DESA LEPPE KECAMATAN SOROPIA KABUPATEN KONAWE) - Setiyawati, Setiyawati; Siang, Roslindah Daeng; Sidiq, Azwar; Yusuf, Sarini; Risfandi; Rosmawati, (Jurnal Perikanan Pantura (JPP), 2026)
This study aims to analyze the market and financial feasibility aspects of octopus collection businesses in UD. Independent in Leppe Village, Soropia Subdistrict, Konawe Regency. This study was conducted in November 2024 and employs a case study approach on the octopus collection business. Data collection techniques included observation, interviews, documentation, and literature review. The data analysis method used in this research is quantitative descriptive analysis, utilizing formulas for total cost, total revenue, R/C ratio, NPV, IRR, and Payback Period. The market aspect findings indicate that the average quantity of octopus offered by UD Mandiri to PT Najwa Bahari is 3,151.6 kg per year, the price per kilogram of octopus varies, and the distribution channel is simple. Regarding the financial aspect, the investment cost is IDR 24,210,000 per year, the total cost of the octopus collection business is IDR 160,791,780 per year, the total revenue for all octopus sizes is IDR 175,979,000 per year, the income or profit is IDR 15,187,200 per year, the R/C ratio is 1.09 per year, the NPV is IDR 82,458,678, the IRR is 0.62 or 62%, and the PP is 1.6 years. Based on both market and financial aspects, the octopus collection business at UD Mandiri is feasible to operate.